The Imprints Of Galactic Environment On Cluster Formation and Evolution. Issue Volume 12:Issue S316(2015) (31st March 2017) - Adamo, Angela
Abstract: Young star clusters (YSCs) appear to be a ubiquitous product of star formation in local galaxies, thus, they can be used to study the star formation process at work in their host galaxies. Moreover, YSCs are intrinsically brighter that single stars, potentially becoming the most important tracers of the recent star formation history in galaxies in the local Universe. In local galaxies, we also witness the presence of a large population of evolved star clusters, commonly called globular clusters (GCs). GCs peak formation history is very close to the redshift ( z ~ 2) when the cosmic star formation history reached the maximum. Therefore, GCs are usually associated to extreme star formation episodes in high-redshift galaxies. It is yet not clear whether YSCs and GCs share a similar formation process (same physics under different interstellar medium conditions) and evolution process, and whether the former can be used as progenitor analogs of the latter. In this invited contribution, I review general properties of YSC populations in local galaxies. I will summarise some of the current open questions in the field, with particular emphasis to whether or not galactic environments, where YSCs form, leave imprints on the nested populations. The importance of this rapidly developing field can be crucial in understanding GC formation and possibly the galactic environment condition where this ancient population formed.